COVID-19-associated cavernous sinus thrombosis: a case report (Ukrainian Journal of Ophthalmology, 2025)
This paper describes a case of cavernous sinus thrombosis. The condition developed in a patient who had been treated for confirmed COVID-19. Left eye examination findings were as follows: amaurosis; absence of periorbital skin sensation;  signs of orbital cellulitis; ptosis; chemosis; total ophthalmoplegia; exophthalmos; decreased corneal sensation; widened pupil; and absence of pupil light reflex. In addition, ophthalmoscopy showed diffused retinal and optic disc edema. The patient had an atypical clinical course which could not be clearly identified as septic or aseptic, and his elevated D-dimer level could indicate a potential relationship between this condition and COVID-19.
Keywords: COVID-19; ocular symptoms of COVID-19; COVID-19-associated coagulopathy; cavernous sinus thrombosis